PERLINDUNGAN HUKUM MASYARAKAT ADAT TERHADAP ASAS DOMAIN VERKLARING DALAM PERATURAN PERUNDANG UNDANGAN TENTANG BANK TANAH - Muhamad Rafly (Magister Hukum Universitas Semarang, 2023)
This research aims to analyze the fundamental issues of domein verklaring in the legislation regarding land banks concerning communities and to examine the legal protection for communities regarding the establishment of land banks. The creation of the Land Bank intended to provide land for public purposes may ironically escalate agrarian conflicts instead. The verklaring domain principle which contained in the land bank concept defined that land whose ownership cannot be proven will become the state's property. This will certainly endanger customary law communities and the concept of a land bank interpreting the state as owning land is contrary to Article 33 paragraph (3) of the 1945 NRI Law, where the State is tasked with regulating natural resources. The results of this research show that there are elements of the domein verklaring principle in the land bank legislation. Thus, the land bank needs to be canceled through an application for judicial review to the Constitutional Court. The novelty in this research is legal protection for indigenous peoples by the establishment of indigenous people laws and submitting judicial review applications to the Constitutional Court.